The research clinical and instrumental methods of examination of athletes related to the process of intervertebral disk degeneration and stenosis - Tyshchenko, V.; Ksenzov, T.; Odynets, T.; Bogoslav, Т. V.; Ksenzov, A.; Hlukhov, I.; Drobot, K.; Богослав, Тетяна Вікторівна (My University, 2024)
Aim: To determine the level structure of the graph model of the system of clinical and instrumental indicators of athletes with herniated intervertebral discs complicated by spinal stenosis, and to determine the regression model for these indicators. Materials and Methods: This observational study involved 64 athletes (14 – rugby players, 16 – handball players, 15 – basketball players, 19 – football players) with intervertebral disc herniation, complicated by stenosis of spinal canal. Research methods: visual method to evaluate the likelihood of a data set’s normal distribution; correlation and regression analysis; method for determining the ordinal function of a graph through the application of an adjacency matrix, specifically utilizing Demucron’s algorithm. This process is accompanied using a topological sorting of the graph. Results: The results showed the lack of correlation between age and VAS, muscle strength and VAS, as well as VAS and the channel space; little feedback between age and the channel space; weak positive relationship between size of herniated intervertebral disc had a with the length of the illness. The data showed, strong feedback was observed for hernia size and the channel space, hernia size and muscle strength, the channel space, and length of the illness. Conclusions: The evaluation on the complexity and depth of the interconnections between clinical and instrumental metrics in athletes was conducted. The hierarchical organization within the graphical representation was ascertained. A predictive regression model delineating the correlations between clinical and instrumental variables in patients suffering from herniated intervertebral discs, with the complication of spinal canal stenosis was established.
Keywords: athletes; stenosis of spinal canal; regression model; demucron’s algorithm